MANAJEMEN PENGENDALIAN DAN KEPEMIMPINAN PEREMPUAN - Dumyati (Journal Ilmu Sosial, Politik dan Pemerintahan, 2023)
In the public sector, in terms of quantity, there is still a very small number of women who get space and opportunities to occupy strategic positions because to reach the peak of their careers they are still faced with male domination. One of the positive impacts of special attention to women is the expansion of the sector of women's activities into the world of politics. This paper intends to describe the management, control and leadership of women in the People's Welfare Sector, Ilir Barat I District Office, Palembang City. In this study, it is shown that gender has an influence on the characteristics of a leader to implement a management control system. Using a descriptive qualitative research approach, this study concludes that female leaders already have standards or goals and targets that must be achieved in carrying out management functions by holding meetings so that subordinates know what targets will be achieved and increase the leader's knowledge to equate perceptions of tasks with each member. so that there are not many perceptions that are built by routinely coordinating to get agreement on each task. So women's leadership styles are clearly visible and have an influence on the management control system applied in the business entity, both in terms of result control, action control, personnel and cultural control. In addition, this research found that leadership style and implementation of control systems management is affected indirectly from historical experience the leader.